International Council of Nurses President Annette Kennedy reflects on her 4‐year tenure as president. (25th November 2021) - Kennedy, Annette
Abstract: Annette Kennedy's four year term as President of the International Council of Nurses ended during the organisation's virtual Congress in November. Here she writes about her time in office and the state of the world's nursing after 2 years of the pandemic. She acknowledges the strains that COVID‐19 has put on nursing but affirms that nurses and nursing have come through the pandemic as a stronger, more influential and more cohesive profession.